NUTRITION EDUCATION CURRICULUM FOR TRAINING PHYSICIANS IN MEDICAL COLLEGES OF PAKISTAN: Nutrition Education Curriculum - Mansoor, Sumreena (Pakistan Armed Forces Medical Journal, 2015)
Objective: This study was designed to critically examine the place and extent of the nutrition education component in undergraduate medical curriculum. Study Design: We have employed two-phase, sequential mixed methods approach in which we based our knowledge claims on problem centered pragmatic grounds. Place and Duration of Study: Nutrition education for training physicians (NEP 2013 survey) was administered for six months from February 2013 till July 2013 through email to Dean/Principal, Head of department of Biochemistry in all medical colleges of Pakistan. Recipients had the option of filling out and returning the survey via email or fax. Material and Methods: Single-stage sampling procedure was used for survey. Non-probability convenience sampling technique was used for interviews. Research questions addressed the course information, organization and implementation of the nutrition curriculum in medical institutions of Pakistan. We tried to enhance the reliability of the survey information where possible by gathering data directly from individuals involved in the development and/or implementation of the nutrition curriculum. Results: On average, in fourteen of the 15 schools students received 10.6 contact hours of nutrition instruction during medical school (range: 2–30 hours). Only 1 school received the required minimum 25-30 hours as recommended by the American National Academy of Sciences. Ninety three percent expressed the need for additional nutrition instruction at their institutions. Conclusion: With the involvement and oversight of faculty with training an interest in nutrition, integration of nutrition education can be successfully accomplished.